On becoming a psychotherapist - Anema, Margaret Catherine (Rhodes University, Faculty of Humanities, Department of Psychology, 1982)
From Introduction: To learn to focus on the other, I first have to learn my natural limits. Unless my natural limits are found, I cannot focus on myself or the other with freedom. I will either draw back or intrude. As I learn my natural limits, I free the energy I previously used in questioning limits. Having recognised that I am bounded, the effect of my released energy is to deepen my space. The infinity which used to lie beyond the horizon is brought into the realm of the human where it can be useful. As a psychotherapist the deepening (that is differentiation) of my own space is very important. It means that the space I share with the other is better explored and better known. The raw data for this thesis is a record of 2Â½ weeks of intensive psychotherapy and 3 weeks of intensive explication. During this time I explored the interrelated themes of my own limits and the particular shadowedness of the space I shared with Tony, the person in psychotherapy with me.
Keywords: Psychotherapist and patient; Psychotherapy; Psychotherapists